Infection of human pegivirus 2 (HPgV-2) is associated with hepatitis C virus but not hepatitis B virus infection in people who inject drugs. (15th May 2019) - Shui, Jingwei; Liu, Wenpei; Liang, Yuanhao; Zhang, Jian; Wan, Zhengwei; Wang, Haiying; Qu, Xiaowang; Tang, Shixing
Abstract : We evaluated the association between human pegivirus -2 (HPgV-2) infection and hepatitis C virus (HCV)/hepatitis B virus (HBV) co-infection in 745 plasma samples collected from HCV-positive but human immunodeficiency virus type one (HIV-1)-negative people who inject drugs in Hunan, China. The prevalence of anti-HPgV-2 was 4.43  % (33/745) and, within this, the HCV 6a genotype showed significantly higher prevalence as compared with the HCV non-6a genotypes, 6.29  % (18/286) vs. 1.69  % (4/236), respectively ( P =0.009). HPgV-2 RNA was detected in 2.15  % (16/745), and was not significantly different between the HCV 6a and non-6a genotypes, 2.45  % (7/286) vs. 2.54  % (6/236), respectively ( P =0.945). HBV single infection did not increase the risk of HPgV-2 infection. Compared with HCV single infection, HCV/HBV co-infection increased the risk of HPgV-2 infection by about three-fold: odds ratio (OR)=3.24 [95  % confidence interval (CI) 1.34–7.82, P =0.014] according to anti-HPgV-2 positivity or OR=3.51 (95  % CI 1.15–10.74, P =0.051) according to HPgV-2 viraemia. HPgV-2 infection did not increase the levels of liver-specific enzymes. Our study provides new findings regarding the association between HPgV-2 and HCV genotypes as well as HCV/HBV co-infection.